Development of membrane reactor for epoxidation of propylene to propylene oxide in a single step process - Sugeng, Triwahyono; Aishah, A. Jalil; Hadi, Nur; Halimaton, Hamdan; Kobayashi, Masayoshi (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/